2020
DOI: 10.1097/md.0000000000020353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin for the management of endometriosis

Abstract: Background: This study aims to explore the effect of melatonin for the management of endometriosis. Methods: We will search electronic databases (Cochrane Library, MEDLINE, EMBASE, CINAHL, Web of Science, Scopus, Allied and Complementary Medicine Database, Chinese Biomedical Literature Database, and China National Knowledge Infrastructure) from their inceptions to the February 29, 2020 without language and publication time limitations. The study identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For endometriosis patients, two randomized, double‐blinded, placebo‐controlled trials showed contradictory results in the analgesic effect of melatonin (Schwertner et al, 2013; Söderman et al, 2022). To systematize the existing data in the literature, a systematic review and meta‐analysis is in progress (P. Chen et al, 2020).…”
Section: Environmentmentioning
confidence: 99%
“…For endometriosis patients, two randomized, double‐blinded, placebo‐controlled trials showed contradictory results in the analgesic effect of melatonin (Schwertner et al, 2013; Söderman et al, 2022). To systematize the existing data in the literature, a systematic review and meta‐analysis is in progress (P. Chen et al, 2020).…”
Section: Environmentmentioning
confidence: 99%